2021
DOI: 10.1108/aaouj-10-2021-0122
|View full text |Cite
|
Sign up to set email alerts
|

School teachers’ perception and challenges towards online teaching during COVID-19 pandemic in India: an econometric analysis

Abstract: PurposeCoronavirus disease 2019 (COVID-19) outbreak has impacted catastrophically every sector of the economy throughout the world. And, the education sector is not leftover from the devastating effects of lockdown, especially in South Asia. It has led to the prolonged closure of schools/universities, subsequently, traditional teaching expeditiously transformed into online teaching. In the light of the events, this study is pertinent to examine teachers’ perceptions of online teaching and the obstacles they fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 20 publications
5
47
0
1
Order By: Relevance
“…The weather and electricity also influenced internet connection stability. These findings align with Kamal and Illiyan (2021) and Almazova et al (2020) studies which note that the several online teaching barriers are students' digital literacy, retention, attention, and facilities. Rasheed et al (2020) and Prasad et al (2018) described that students' self-regulated and technological competency is the students' obstacle during online teaching.…”
Section: Figure 3 the Results Of The Applications That The English Le...supporting
confidence: 88%
See 1 more Smart Citation
“…The weather and electricity also influenced internet connection stability. These findings align with Kamal and Illiyan (2021) and Almazova et al (2020) studies which note that the several online teaching barriers are students' digital literacy, retention, attention, and facilities. Rasheed et al (2020) and Prasad et al (2018) described that students' self-regulated and technological competency is the students' obstacle during online teaching.…”
Section: Figure 3 the Results Of The Applications That The English Le...supporting
confidence: 88%
“…These findings correlate with previous studies on online teaching implementation in the Covid-19 pandemic. Dimaculangan et al (2022) and Kamal and Illiyan (2021) Vol. 2 (3), August 2022 Imleesh et al (2020) admit that the online teaching implementation during the Covid-19 pandemic is not significantly effective.…”
Section: Figure 3 the Results Of The Applications That The English Le...mentioning
confidence: 99%
“…ough teachers have tried to use various platforms (e.g., digital and social media) more than ever to connect and move their work forward, they are finding that these modalities of interaction bring their own sets of limitations [64]. As evident in studies [28,65], due to a lack of technical/ software knowledge, lack of motivation, insufficient training and professional development courses, guidance, or resources, teachers were unprepared to teach online, which exacerbated the problem. Furthermore, the bivariate correlational analysis showed that teachers' pre-pandemic online teaching experience had a significant positive correlation with teachers' confidence (r � 0.354, P value <0.001 * * * ) and satisfaction (r � 0.422, P value <0.001 * * * ) with online teaching, meaning, teachers having pre-pandemic online teaching experiences were likely to be more confident and satisfied with online teaching during the COVID-19 crisis.…”
Section: Discussionmentioning
confidence: 99%
“…us, issues occurred when teachers were going to create interactive learning resources, present those materials online, offer feedback, and conduct formative assessments [27,28]. On the other hand, according to studies [13,23,29,30], the toughest difficulties that teachers faced during online instruction were mobilizing students' learning attention, maintaining classroom discipline, organizing classroom discussion, motivating students, and giving online feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, online learning allows students to interact with learning resources anytime and from any location because learning resources have been packaged electronically and are available online (Mariono et al, 2021). A study by (Kamal & Illiyan, 2021) found that majority of teachers have a positive perception of online education during the Covid-19. In addition, young teachers have more actively engaged in online learning.…”
Section: Introductionmentioning
confidence: 99%